(3MQR GdCbSGes - (3eLghds
(3ChdgG (B:s
(3jS hGdbQBf GdMcje HGdjhe GdehYhO hTGgO heTghO HGdQH GdeYHhO HGMJjGW b Hghd jhe GdeNGa HYde Gdbde HGSe Gddg GdYXje GdCYXes
(3BNQgG (B:s
(3LYdfG Hjfc hHjf GdPjf dG jDefhf HGdBNQI MLGHG eSJhQG aUdi Gddg Ydi SjOfG eMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf(B: 1 / 646s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs